Attitudinal Expressions in Discussion Sections of High-Quality Journals: an Appraisal Analysis - Widhiyanto; Dewi, Desi Surlitasari (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
Numerous studies discuss assessment in academic texts, there remains a significant gap in the literature regarding the specific role of assessment resources in expressing attitudes within the discussion section of high-quality journal articles. This study explores the utilization of attitudinal expressions (the systems of Affect, Judgement, and Appreciation) in the discussion sections of high-quality journal articles. Employing a mixed-methods research approach, the study integrates qualitative and quantitative analyses to better understand evaluative linguistic practices in academic writing. Data were collected from five high-quality discussion sections published in 2024 in Q1 Scopus journals, including TESOL Quarterly, CALL-EJ, English Teaching & Learning, Australian Review of Applied Linguistics, and Asian-Pacific Journal of Second and Foreign Language Education. The qualitative analysis involved thematic coding and iterative development to identify and categorize attitudinal expressions, while the quantitative analysis utilized statistical techniques to measure the frequency and distribution of these expressions. Results indicated that the Judgement system was the most frequently used category (59.60%), followed by Appreciation system (37.50%) and Affect system (4.80%). The Affect system was primarily used to convey feelings and emotional responses, the Appreciation system was to convey evaluations of the research’s impact and significance. The findings suggest that academic authors strategically use evaluative language to assert research significance and engage critically with literature. Pedagogically, this study highlights the importance of teaching advanced academic writing skills, particularly the use of evaluative language, to enhance students’ ability to communicate their research effectively.